Study comparison P-Delta Effect analysis depends on height variation of the building - Heri Istiono; Eka Susanti; Jaka Propika; Azhar Yusuf Ramadhan (Journal of Civil Engineering, Planning and Design, 2022)
Indonesia is an area where three active plates meet, so many areas are prone to earthquakes. To anticipate this and minimize casualties due to earthquakes, earthquake-resistant buildings are needed. Earthquake resistant buildings are the most important thing that needs to be considered, a building structure must be designed to be able to withstand lateral loads such as earthquakes within the limits set by the code/standard. The result of the earthquake load will produce an additional effect on the multi-storey building, namely the P-Delta effect. In this study, the effect of these effects will be analyzed on non-rise buildings and high-rise buildings. Analysis of the P-Delta effect will be calculated on the modeling of three buildings for non-rise buildings (Building models A, B and C) and three highrise building models (Building models D, E and F) and get the results that the P-Delta Effect has an impact on changes structural performance level in Model E Building (56 meters) from Immediate Occupancy to Life Safety